DETEKSI DINI BABY BLUES SYNDROME TERHADAP IBU NIFAS YANG MELAHIRKAN DENGAN CARA SECTIO CAESAREA (SC) DI RSIA MUTIARA BUNDA PADANG PADA TAHUN 2023 - Tia Reza; Febria Nesta; Tati Khairina; Ade Yuli Amelia; Febianne Eldrian (Nusantara Hasana Journal, 2024)
Background: Baby blues syndrome or postpartum blues is an emotional disorder experienced by a woman after giving birth due to emotional stress before and after giving birth. The resolution of baby blues cases so far uses health and psychological approaches. Baby blues syndrome often appears within the first week after delivery and peaks on days 3 to 5 and lasts for 14 days after delivery. Research Objectives:This study aims to determine early baby blues syndrome in postpartum mothers who give birth by Sectio Caesarea (SC) at RSIA Mutiara Bunda Padang. Method: This type of research is categorically descriptive with a cross sectional design involving postpartum mothers who gave birth by sectio caesarea (SC) at RSIA Mutiara Bunda as many as 100 people. The primary data obtained will be through univariate analysis. Results: This study resulted in postpartum mothers who experienced the most baby blues syndrome in the age range of 20-34 years, which was 27 people (31.0%), with the most jobs as housewives as many as 24 people (35.3%). Meanwhile, from the level of education, postpartum mothers who experience baby blues syndrome have the most undergraduate education as many as 16 people (31.4%). Postpartum mothers with primiparous parity experienced baby blues syndrome as many as 19 people (34.0%). Based on the husband and family support questionnaire, postpartum mothers with baby blues syndrome did not receive the most husband support, 20 people (36.0%), but the most received support from family as many as 20 people (25.3%). Conclusion: The results of this study show early detection of postpartum mothers including age, occupation, education, parity, husband support, and family support.